Financial Performance of Savings and Loan Cooperatives in Perspective Fund Management and Governance - Ahmad, Cahyani; Ridho Rahmayanti, Siti; Aggriani Matowa, Regina; Budiawan, Shella (Jurnal Ilmiah Multidisiplin Amsir, 2025)
This study aims to analyze the financial performance of savings and loan cooperatives through a review of ten journals that review liquidity ratios, solvency, profitability, operational efficiency, and quality of cooperative governance. The method used is a literature study by combining analysis of scientific journals and online supporting data, so as to provide a comprehensive picture of the financial stability of the cooperative. The results of the study show that most cooperatives face problems of low liquidity, high dependence on debt, weak profitability, and suboptimal operational efficiency. Some cooperatives are even in the bankruptcy-prone zone based on the Altman Z-Score assessment. On the other hand, cooperatives that consistently apply financial statement analysis, have strong own capital, and implement good governance and transparency are proven to have more stable performance and higher levels of member participation. These findings confirm that improving the quality of accounting human resources, optimizing the use of information technology, discipline of financial ratio analysis, and strengthening risk management are urgent needs to maintain the sustainability of savings and loan cooperatives in Indonesia.